Modulation of the inflammatory response of immune cells in human peripheral blood by oxidized arachidonoyl aminophospholipids - Colombo, Simone (2019)
Aminophospholipids (APL), phosphatidylethanolamine (PE) and phosphatidylserine (PS), can be oxidized upon oxidative stress. Oxidized PE and PS have been detected in clinical samples of different pathologies and may act as modulators of the inflammatory response. However, few studies have focused on the effects of oxidized APL (ox-APL) esterified with arachidonic acid, even though a considerable number of studies have assessed the modulation of the immune system by oxidized 1-palmitoyl-2-arachidonoyl-sn-3-glycerophosphocholine (OxPAPC). In the present study, we have used flow cytometry to evaluate the ability of oxidized PAPE (OxPAPE) and PAPS (OxPAPS) to promote or suppress an inflammatory phenotype on monocytes subsets and myeloid dendritic cells (mDCs). The results indicate that OxPAPE increases the frequency of all monocyte subpopulations expressing TNF-α, which promotes an inflammatory response. However, immune cell stimulation with OxPAPE in the presence of LPS results in a decrease of TNF-α expressed by classical monocytes. Incubation with OxPAPS and LPS induces a decrease in TNF-α produced by monocytes, and a significant decrease in IL-1β expressed by monocytes and mDCs, indicating that OxPAPS reduces the LPS-induced pro-inflammatory expression in these populations. These results show the importance of OxPAPE and OxPAPS as modulators of the inflammatory response and demonstrate their possible contribution to the onset and resolution of human diseases related to oxidative stress and inflammation.